IMPROVING HEALTH BEHAVIOR IN THE COMMUNITY THROUGH EMPOWERING HEALTH-AWARE COMMUNITIES - Kurniawan, Vendi Eko; Putra, Kusuma Wijaya Ridi; Setiawan, Roni (Journal of Indonesian Public Health Service, 2024)
This article reports on a community service program conducted in Nglajur Hamlet, Tugusumberejo Village, Peterongan District, Jombang Regency, from April 29 to May 25, 2024. The program aimed to improve public health behavior by empowering a health-aware community. The initiative involved a series of activities, including health education on waste management, community service efforts, education on common health issues such as hypertension and stroke, health screenings, and providing home care for the elderly. Led by three lecturers and 23 students from the Bachelor of Nursing Science Study Program at the College of Health Sciences of Husada Jombang, the program successfully engaged the local community in each activity. The active participation of community members reflected the program's effectiveness in fostering collective responsibility and promoting sustainable health behaviors. The results underscore the importance of community empowerment in achieving long-term improvements in public health.